FRI0295 High risk of idiopathic osteonecrosis in sle patients with high antiphospholipid score and hypertriglyceridemia. (15th June 2017) - Hisada, R; Kato, M; Ohnishi, N; Kono, M; Tanimura, S; Sugawara, E; Nakamura, H; Ohmura, K; Shimamura, S; Fujieda, Y; Oku, K; Bohgaki, T; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) patients are prone to develop idiopathic osteonecrosis (ION) compared to other connective tissue disease patients or healthy subjects. ION has been shown to occur as a result of ischemia, however, the involvement of antiphospholipid antibodies (aPL) in its pathophysiology remains to be elucidated. In the last years, our group introduced a quantitative marker of aPL "antiphospholipid score (aPL-S)", which well reflected the risk of developing thrombosis [1]. Objectives: We aimed to identify the impact of aPL on the development of ION using aPL-S. Methods: A single center retrospective study comprising 82 consecutive patients who were diagnosed SLE at the Rheumatology department of Hokkaido University Hospital and underwent magnetic resonance imaging (MRI) of hip joints from January 2000 to December 2016. Among all the enrolled patients, aPL-S, which is calculated from 0 to 86, as well as classical risk factors for ION were evaluated. Results: All 82 patients (13 males and 69 females) were given glucocorticoids. ION of the femoral head was diagnosed by MRI scan in 37 patients. Male (ION(+): ION(-) 10/37 (27%) vs 3/45 (7%), p=0.016), malar rush (ION(+): ION(-) 22/37 (59%) vs 16/45 (36%), p=0.045), aPL positivity (ION(+): ION(-) 22/37 (59%) vs 15/45 (33%), p=0.026), high aPL-S (>30) (ION(+): ION(-) 9/37 (24%) vs 3/45 (7%), p=0.031), hypertriglyceridemia (fasting triglyceride levels >150 mg/dL) (ION(+): ION(-) 23/37 (62%) vs 12/45 (27%), p=0.002) and high dose of glucocorticoids (equivalent to 0.8mg/kg or more prednisolone) (ION(+): ION(-) 34/37 (92%) vs 21/45 (47%), p<0.001) were identified as risk factors for ION at univariate analysis. Multivariate analysis confirmed high aPL-S (OR 5.27; 95% CI 1.08 to 34.52, p=0.040), hypertriglyceridemia (OR 5.66; 95% CI 1.79 to 20.73, p=0.003) and high dose of glucocorticoids (OR 16.11; 95% CI 4.01 to 92.54, p<0.001) as independent variables. Of note, in 6 patients who had both high aPL-S and hypertriglyceridemia, 83% (5/6) developed ION (Figure 1 ). Conversely, systemic lupus erythematosus disease activity index and pulsed methylprednisolone therapy were not identified as risk factors for ION. Conclusions: We newly identified high aPL-S as a risk factor for ION. Furthermore, SLE patients who have both high aPL-S and hypertriglyceridemia are at very high risk of ION. These findings suggest the involvement of microvascular occlusion in the pathophysiology of ION in SLE. References: Otomo K, et al. Efficacy of the antiphospholipid score for the diagnosis of antiphospholipid syndrome and its predictive value for thrombotic events. Arthritis Rheum. 2012. Disclosure of Interest: None declared